Effects of Executive Function Training on Attentional, Behavioral and Emotional Functioning and Self-Perceived Competence in Very Preterm Children: A Randomized Controlled Trial - van Houdt, Carolien A.; Aarnoudse-Moens, Cornelieke S. H.; van Wassenaer-Leemhuis, Aleid G.; Laarman, A. R. Céleste; Koopman-Esseboom, Corine; van Kaam, Anton H.; Oosterlaan, Jaap (Frontiers in Psychology, 2019)
Objective Very preterm children have poorer attentional, behavioral and emotional functioning than term-born children. Problems on these domains have been linked to poorer executive function (EF). This study examined effects of a game-formatted, comprehensive EF training on attentional, behavioral and emotional functioning and self-perceived competence in very preterm children. Study design Eighty-five children participated in a multi-center, double-blind, placebo and waitlist-controlled randomized trial. Children were recruited from neonatal follow-up units of two academic medical centers in The Netherlands. Eligible for inclusion were 8 to 12 year old children born very preterm (<30 weeks of gestation) and/or with extremely low birthweight (<1000g) with parent reported attention problems. Children were randomly assigned to one of three treatment arms: EF training, placebo training or waitlist. The EF and placebo training involved a 6 weeks, 25 (30-45 minutes) sessions training program. Attentional functioning (Attention Network Test), behavioral and emotional functioning (parent and teacher Strengths and Difficulties questionnaire) and self-perceived competence (Self-Perception Profile for Children) were assessed at baseline, at the end of the training program and five months after the training was finished. Data analyses involved linear mixed model analyses. Results Children in the EF training arm significantly improved on all training tasks over the course of the EF training program. Despite these improvements on the EF training tasks, there were no significant differences over time on any of the outcome measures between the three treatment arms, indicating that this computerized EF training program had no beneficial effects. Conclusions Although there were significant improvements in the EF training tasks, there was no generalization of these improvements to any of the outcome measures. Thus, our findings do not support the use of computerized EF training programs. Future research should investigate effectivity of more ecologically valid, real-world like EF training programs.